2000
DOI: 10.1021/ja000988x
|View full text |Cite
|
Sign up to set email alerts
|

Probing Individual Steps of Dynamic Exchange with 31P EXSY NMR Spectroscopy:  Synthesis and Characterization of the [E7PtH(PPh3)]2- Zintl Ion Complexes [E = P, As]

Abstract: Ethylenediamine (en) solutions of E7 3- (E = P, As) react with Pt(PPh3)2(C2H4) in the presence of 4,7,13,16,21,24-hexaoxa-1,10-diazobicyclo[8.8.8]hexacosane (2,2,2-crypt) to give the transition-metal Zintl ion complexes [P7PtH(PPh3)]2- (1) and [As7PtH(PPh3)]2- (2) as isomorphic [K(2,2,2-crypt)]+ salts, respectively. The hydride ligand originates from the solvent, and deuterium labeling studies show that the order of hydrogen sources follows the sequence en > CH3CN > DMSO > DMF in the synthesis of 1. The [E7PtH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
2
34
0
2
Order By: Relevance
“…Computational investigation into the mechanism of exchanging the metalated phosphorus atom identified an η 1 ‐η 2 ‐η 1 “walking” mechanism as was previously reported for other η 1 ‐P 4 complexes and the heptaphosphanortricyclene‐P 7 3− moiety in [η 2 ‐P 7 {PtHPPh 3 }][K(2,2,2‐crypt)] 2 . The intermediate η 2 ‐P 4 complexes [CpFe(CO)(L)(η 2 ‐P 4 )] + at the BP86/def‐SV(P) level of theory with D3(BJ) dispersion correction are located 20 and 25 kJ mol −1 higher in energy than the structurally characterized η 1 ‐analogues for L=CO and PPh 3 .…”
Section: Figurementioning
confidence: 61%
“…Computational investigation into the mechanism of exchanging the metalated phosphorus atom identified an η 1 ‐η 2 ‐η 1 “walking” mechanism as was previously reported for other η 1 ‐P 4 complexes and the heptaphosphanortricyclene‐P 7 3− moiety in [η 2 ‐P 7 {PtHPPh 3 }][K(2,2,2‐crypt)] 2 . The intermediate η 2 ‐P 4 complexes [CpFe(CO)(L)(η 2 ‐P 4 )] + at the BP86/def‐SV(P) level of theory with D3(BJ) dispersion correction are located 20 and 25 kJ mol −1 higher in energy than the structurally characterized η 1 ‐analogues for L=CO and PPh 3 .…”
Section: Figurementioning
confidence: 61%
“…Rather different is the dynamics of 120 in solution, where the PtH(PPh 3 ) fragment shifts from the top to the bottom of the P 7 cluster (η 2 –η 4 –η 2 shift) and spins in the P 4 face in a concerted process to give apparent C 2 V symmetry (Scheme ). Eichhorn's group have shown that shift is 20 times faster than spinning in cluster 120 …”
Section: Isomerisations and Rearrangementsmentioning
confidence: 99%
“…Coalescence of the 31 P NMR signals could only be extrapolated to occur above 373 K; nevertheless, the EXSY 31 P{ 1 H} spectrum at 333 K revealed correlations between the broadening signals, thus confirming a dynamic exchange between the isomers (see experimental section and Figure 6 therein). 22 Line shape analysis of VTP 1 H NMR spectra allowed the determination of the first-order rate constant k(T) of the stereo-conversion at the variable temperature T. The Eyring plots Figures 3 and 5). 23 Almost the same value (17.0 kcal/mol) was obtained by line shape analysis of the VTP 31 P NMR spectra (Table 1, Figures 5 and 6).…”
Section: Resultsmentioning
confidence: 99%